(untitled) (Journal of the Bangladesh Agricultural University, 2017)
Clinical detection of Foot and Mouth Disease in the cattle which study was carried out in Kapasia upazila under Gazipur district during from February 2011 to January 2012 and identifying the potential risk factors associated with the studies in Kapasia, Gazipur. A total of 315 infected cattle of different age, sex were examined in the upazila veterinary development center of Kapasia in Gazipur district. Total 86 (27.30%) cattle were infected with FMD on the basis of clinico-epidemiological determinants. The effect of season, Breed, Age, and sex of cattle on the incidence of the disease was discussed. It was observed that rural farming system (30.43%) was more susceptible than intensive farming (21.30%) system of cattle. Old animals (33.15%) were more susceptible than adult (21.81%) and young (15.71%). The prevalence of disease was found significantly (P < 0.05) higher in male (33.65%) than in female (24.17%). It was observed that local breed cattle (35.48%) were more susceptible than cross-breed cattle (15.50%). Seasonal variation of the disease was significant in the study area. The infection was less in summer (11.63%) and increasing in rainy season (25.58%) but gradually increased in late period of winter season (62.80%). This report will help to prioritize and control strategies against Foot and Mouth diseases from Kapasia upazila at Gazipur District in Bangladesh. J. Bangladesh Agril. Univ. 14(2): 185-190, December 2016